The Influence of Artificial Intelligence Implementation on Leadership Effectiveness and Human Resource Performance in Higher Education Institutions - Purnomo, D Purnomo (Best Journal of Administration and Management, 2026)
The rapid digital transformation in higher education institutions has accelerated the adoption of Artificial Intelligence (AI) to improve managerial effectiveness and workforce productivity. However, empirical evidence regarding the integrated relationship between AI implementation, leadership effectiveness, and human resource performance remains limited. This study aims to examine the direct effect of AI implementation on leadership effectiveness and human resource performance, as well as to analyze the mediating role of leadership effectiveness in this relationship. This research employed a quantitative explanatory design using a survey method. Data were collected from academic leaders and administrative staff at higher education institutions through structured questionnaires distributed using purposive sampling. The research instruments were measured using a five-point Likert scale and tested for validity and reliability. Data were analyzed using Structural Equation Modeling (SEM) to evaluate both direct and indirect relationships among variables. The findings indicate that AI implementation has a positive and significant effect on leadership effectiveness and human resource performance. Leadership effectiveness also significantly influences employee performance and partially mediates the relationship between AI implementation and human resource outcomes. These results demonstrate that AI serves as a strategic enabler, while effective leadership ensures optimal translation of technological adoption into measurable performance improvements. In conclusion, sustainable performance enhancement in higher education requires the integration of intelligent technology and adaptive leadership capability. Future research is recommended to apply longitudinal designs and explore moderating variables such as digital organizational culture and institutional governance structure.